2021
DOI: 10.1039/d1lc00497b
|View full text |Cite
|
Sign up to set email alerts
|

Human neuromuscular junction on micro-structured microfluidic devices implemented with a custom micro electrode array (MEA)

Abstract: Microfluidic devices were coupled with custom MEA and used for co-culture of human motor neurons and muscles. This allowed to assess human NMJ activity by electrical stimulation of axons and recording of subsequent muscle action potentials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 58 publications
0
22
0
Order By: Relevance
“…Such a multi‐functional platform is promising for the development of technologies to characterize neural circuits and neuromuscular units with higher sensitivity as compared to the traditional approaches, such as intracellular calcium imaging. [ 335 ]…”
Section: Microfluidics For Bio‐actuatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such a multi‐functional platform is promising for the development of technologies to characterize neural circuits and neuromuscular units with higher sensitivity as compared to the traditional approaches, such as intracellular calcium imaging. [ 335 ]…”
Section: Microfluidics For Bio‐actuatorsmentioning
confidence: 99%
“…Duc et al exploited soft lithography and custom MEAs to engineer a microfluidic model of human neuromuscular junction on a specific pattern of electrodes to stimulate presynaptic axons and record postsynaptic muscle activity (Figure 6F). [335] In this platform the group demonstrated that not only the achievement of a mature and functional neuromuscular modeling via microstructuring of the chip and the cell growth substrates, but also that the electrical activation of motor neurons triggered recordable extracellular muscle action potentials. Such a multi-functional platform is promising for the development of technologies to characterize neural circuits and neuromuscular units with higher sensitivity as compared to the traditional approaches, such as intracellular calcium imaging.…”
Section: Microfluidics In Muscle Tissue Engineeringmentioning
confidence: 99%
“…In 2005, Taylor and colleagues reported a microfluidic multi-compartment chamber that can be easily replicated by soft-lithography ( Taylor et al, 2005 ) and installed on cell culture dishes (e.g., culture dish, glass coverslip, and recording chips). Since then, there have been various cell culture assays including axon growth ( Park et al, 2014 ; Taylor et al, 2015 ), synapse manipulation ( Taylor et al, 2010 ), synapse remodeling ( Nagendran et al, 2017 ), axonal transport ( Moutaux et al, 2018b ), stem cell-derived neuron migration ( Lee et al, 2014 ), and neuron/non-neuronal cell (e.g., glia, cardiomyocyte, and muscle fiber) interaction ( Duc et al, 2021 ; Hosmane et al, 2010 ; Park et al, 2012 ; Takeuchi et al, 2011 ). More applications can be found elsewhere ( Neto et al, 2016 ).…”
Section: Cell Patterning Techniquesmentioning
confidence: 99%
“…On the MEA, the DG-CA3-CA1 ( Brewer et al, 2013 ) and cortical-thalamic network ( Kanagasabapathi et al, 2012 ) were developed, and their spike propagation and burst behavior were examined. Furthermore, different cell types, such as cardiomyocytes with neurons in the peripheral nervous system ( Takeuchi et al, 2011 ), myoblasts with motor neurons ( Duc et al, 2021 ), or stem cell-derived neurons with primary neurons in the central nervous system ( Takayama et al, 2012 ) were also co-cultured to interrogate their interactions via electrophysiological observation.…”
Section: Microelectrode Array For Analyzing the Functional Connectivi...mentioning
confidence: 99%
“…The first generation of these body-on-a-chip-models already exists [ 241 ], and the incorporation of MEAs into the models can provide important information on the electrical activity of not only the brain-part but also other tissues such as the heart [ 242 ], retina [ 243 ] and pancreatic beta cells [ 244 ]. Furthermore, connecting peripheral neurons to CNS neurons in a body-on-a-chip is an interesting option [ 245 ], and the function of the human neuromuscular junction was recently modeled in a microfluidic device on MEA [ 246 ].…”
Section: Future Directionsmentioning
confidence: 99%